ORGANIZATION AND PROCESS OF TEACHING ENGLISH TO YOUTH UNDER PROBATION: INTERNATIONAL EXPERIENCE AND IMPLICATIONS FOR UZBEKISTAN (SCIENCE TIME JOURNAL, 2026)
Youth under probation often stand at a fragile intersection between accountability and opportunity. Educational exclusion, unstable family environments, and limited employability frequently shape their trajectories. International research demonstrates that structured educational interventions within correctional and probation systems significantly reduce recidivism and improve reintegration outcomes (Davis et al., 2013). Among these interventions, English language instruction occupies a unique position in non-English-speaking countries, functioning both as an employability tool and as a medium for rebuilding learner identity. This article examines global experience in organizing and delivering English language education to justice-involved youth under community supervision and discusses its relevance to the developing probation framework of Uzbekistan. Drawing upon international standards, empirical research, and national policy developments, the paper proposes an organizational and procedural model adapted to the Uzbek context.